The Comparison on 21st Century Skills of Early Childhood in Four Schools in Yogyakarta - Munastiwi, Erni (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2021)
Purpose – This study aims to determine differences in 21st-century abilities, including critical thinking, creative thinking, communication skills, and collaboration skills, in 4 schools in the Yogyakarta region. This research is a comparative survey with a research sample of 60 students.Design/methods/approach – The data collecting techniques used in interviews with questionnaires consist of 4 21st century abilities: critical thinking skills, creative thinking, communication skills, and collaboration skills.Findings – The survey results showed differences in 21st-century abilities between schools AR with RA, AR with TY, RA with TY, RA with RB, and TY with RB. The t-test, where the sig prove this.t value <0.05 is obtained in a row on the creative thinking ability of 0.001; 0.049; 0.00; 0.001; 0.024. Ability to think creatively in succession 0.003; 0.009; 0.000; 0.009; 0.005. 0.000 successive communication skills; 0.011; 0.000; 0.000; 0.003. Collaboration ability 0.002 consecutively; 0.001; 0.000; 0.003; 0.000. Then there is no difference between AR and RB schools. The value of sig evidences this. t > 0.05 in a row on critical thinking skills, creative thinking, communication skills, and collaboration skills 0.781; 0.702; 0.540; 0.624. The difference in ability is influenced by the learning method used.Research implications/limitations – All study respondents were from four schools in Yogyakarta, Indonesia, which might limit the generalizability of the findings.Practical implications – This research guides stakeholders of an early childhood education institution to take strategic policies in the 21st century.Originality/value – This study contributes to the survey of differences in the abilities of early childhood in the 21st century in terms of different early childhood education institutions. Paper type Research paper